2017
DOI: 10.1039/c7ce01271c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of aqueous glycine solutions

Abstract: Simulations of glycine aqueous solutions have been carried out to study the effect of increasing solute concentration on the aggregation of glycine zwitterions. AMBER force field coupled with three atomic charge sets was employed for the simulations of the aqueous solutions. The number of glycine monomers in solutions rapidly decreases with increase in concentration. The properties of the glycine clusters in the solutions were studied. It was shown that the clusters are strongly hydrated entities with a liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…3C: this is the concentration at which the solution will crystallize immediately, without any water evaporation. The corresponding critical supersaturation ratio (S*) is 1.08 as the saturation concentration (C sat ) for glycine in aqueous solution at 25 1C is 3.33 M. 29 This value is in good agreement with the one determined by a previous study based on microdroplet crystallization experiments (1.12 at 21 1C). 28 Fig.…”
Section: Resultssupporting
confidence: 87%
“…3C: this is the concentration at which the solution will crystallize immediately, without any water evaporation. The corresponding critical supersaturation ratio (S*) is 1.08 as the saturation concentration (C sat ) for glycine in aqueous solution at 25 1C is 3.33 M. 29 This value is in good agreement with the one determined by a previous study based on microdroplet crystallization experiments (1.12 at 21 1C). 28 Fig.…”
Section: Resultssupporting
confidence: 87%
“…This is the first time that Raman spectrum of pre-nucleation aggregates was identified, and this provides us a crucial link to the theoretical investigation of its structure. Recent studies based on molecular dynamics simulation suggested the presence of aggregates at high concentration of glycine aqueous solution, 34,38,39 which agree with our observation. In this work, we were determined to gain an insight into the conformations of the pre-nucleation aggregates.…”
Section: Resultssupporting
confidence: 92%
“…it is the simplest amino acid, its crystallization process has been shown rather complex and is under active debates. [30][31][32][33][34][35][36] Fig. 1c-f shows a series of Raman spectra obtained in-situ during a single crystal nucleation of glycine which highlights the dynamic nature of crystal nucleation (see the movie SI1 for the whole experiment).…”
Section: Resultsmentioning
confidence: 99%
“…While it is impossible to determine the structure of the aggregates based on the C=O stretching frequency of P ox alone, this information is nevertheless sufficient to allow identification of the underlying mode of interaction. For example, should proline (glycine) molecules aggregate through dimerization via H-bond formation, as that depicted in several studies, 3437 we expect to observe a red-shift in the stretching frequency of the C=O oscillator of P ox in 2.0 M proline (glycine) solution in comparison to that in D 2 O. This is because in such dimers the –NH 2 + group of P ox would interact with the –COO − group of another amino acid (e.g., proline), effectively decreasing the positive charge density on the N atom of P ox .…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, these results are in agreement with previous studies indicating that association of proline (glycine) molecules occurs through dimerization. 3437…”
Section: Resultsmentioning
confidence: 99%